Historical policy review on disability (Research Nepal Journal of Development Studies, 2018)
Historical Policy Review on disability is a comprehensive historical policy analysis of past, barriers, and developing trend and disability in Nepal. People with disability in Nepal seems to be suffering from different dimensions. The article is focused on history and policy led aspects in Nepal. Are the policies sufficient? This article seeks to objectively identify the policy gaps and historical development of institutional support for people with disability in Nepal. Methodologically, the article is a descriptive analysis of disability in Nepal. The article has adopted internet based library method to review the policy gaps and history of development trend of support for people with disability. In conclusion, it is obvious from the review of policies and international conventional commitments that Nepal has sufficient policies regarding the people with disability. The most serious issue is good governance of organizations. Lack of responsibility, accountability and transparency are still a problem though there are many policies emphasizing the solutions to these problems. This means the implementation aspects of disability are very disappointing. Historically, mythological, and cultural aspects of disability are not defined scientifically. Therefore, the same problems anomalies are seen in contemporary lives of people with disability.Research Nepal Journal of Development Studies Vol.1(1) 2018 73-82